THE IMPACT OF THE GLOBAL FINANCIAL CRISIS ON THE PUBLIC AND PRIVATE FINANCES IN ROMANIA - SANDA GHEORGHE GABRIEL; ENEA CONSTANTA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
If the exit from the crisis is linked to the productivity, the technological boom, the orientation should take place by sectors with high growth potential. The idea is that the power of the Government to rely on increasing economic value and implementing effective measures to redress and not on fiscal destructive policies that can block even more the economic development. In order to exit from the economic and financial crisis it is necessary to identify the risks and vulnerabilities of the financial system as a whole. However, the emergence of malfunctions such as inaccurate assessment of risks and the inefficiency with which capitals are allocated can affect the equilibrium of the financial structure. Some solutions to overcome the negative effects of the global crisis to which has been submitted to Romania are represented by the design and implementation of strong macroeconomic frameworks, reviewing and improving the capacity of institutional, organizational level, to ensure a sustainable and environmentally sound growth of the economy in the long run, for the benefit of the society in general. The real cause of the economic crisis, whether it is called: recession, crisis, economic depression or another name, the content and the effect of the crisis are the same, however, can be solved if the policy makers choose to stabilize the financial conditions and to find solutions stimulus, achieving strong macroeconomic frameworks, improving the institutional capacity to ensure a sustainable and favorable growth of the economy, the society in general.